Sea level change and archaeological site locations on the Dundas Island Archipelago of north coastal British Columbia - McLaren, Duncan (2008)
Coastal archaeological sites dating to the late Pleistocene and early Holocene are rare on the northwest coast of North America, as they are in many regions of the world, due to changing environmental factors, in particular glacial isostasy and eustasy, resulting in low visibility and survival of archaeological deposits. This dissertation outlines methods and results used to locate late Pleistocene and early Holocene archaeological sites on the Dundas Island Archipelago on the Northwest Coast culture area of British Columbia, Coast Tsimshian Territory, where archaeological sites older than 5,000 years BP are not known. Part of the reason for this is that masses of glacial ice accumulated on the Cordilleran Mountains of North America during the last glacial maximum, which depressed mainland coastal regions isostatically in relation to sea levels. As a result of lateral displacement of subcrustal material, areas to the west of the Cordillera bulged and landforms were raised relative to the sea. With deglaciation, the depressed crust began to rebound and the forebulge subsided resulting in rapidly dropping sea levels along the mainland to the east and rapidly rising sea levels along outer coastal islands to the west. These processes occurred in concert with sea levels that began rising eustatically following the last glacial maximum. Between the inner and outer coasts lies the Dundas Island Archipelago. This research project hypothesized that the study area was close to a sea level hinge lying between these two regions with very different sea level histories. With less significant shoreline movement, it was further anticipated that shoreline situated archaeological sites dating to the late Pleistocene and early Holocene might be found in close proximity, although slightly higher than the present day shoreline. This dissertation addresses the following question: Where are late Pleistocene and early Holocene archaeological sites situated on the Dundas Island Archipelago? To address this question, this dissertation ...